Extract, Transform, and Load data from Legacy Systems to Azure Cloud - Jephte, Ioudom Foubi (2021)
Internship report presented as partial requirement for obtaining the Master’s degree in Information Management, with a specialization in Knowledge Management and Business Intelligence